Education in times of pandemic: Perspectives of the emergency remote teaching model in Colombia - Acevedo Tarazona, Álvaro; Valencia Aguirre, Ana Cecilia; Ortega Rey, Angie Daniela (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2021)
Objective: Due to the educational crisis caused by the COVID 19 pandemic, this article explores the impact that the Emergency Remote Teaching (ERT)  model has had on the Colombian educational context, as well as on the actors involved in this academic shift towards virtuality. Originality/contribution: We consider of utmost importance to understand the impact that the Emergency Remote Teaching (ERT)  model has had on the educational processes and their actors during the recent COVID-19 pandemic in Colombia. From the analysis of the positive and negative implications of this teaching model, it is possible to identify different shortcomings of the national education system in this transition to virtuality. Some opportunities for improvement are also proposed. Method: this research was developed under a qualitative methodology with interpretative orientation. The historical-hermeneutic approach guided the analysis of the information collected, since this research seeks to understand the educational experience in times of pandemic. Strategies/information collection: The collection of information was done through documentary review of online sources, press and semi-structured interviews. For the documentary analysis and review of periodical publications, information that circulated during 2020 in national and international newspapers such as El Tiempo, Revista Semana, BBC News Mundo and CNN en Español was used. The collection of online documents was carried out through the Google Scholar platform. The interviews were open-ended, which allowed us to start from a generative question in order to avoid biasing the story and, at the same time, to foster new questions and expand the narrative. The criteria for the selection of the participants had to do with their institutional affiliation to the Universidad Industrial de Santander as students and their socioeconomic status. Conclusions: From this article it is possible to conclude that despite government efforts to promote an online learning environment and the willingness of teachers and students to adapt to the new virtual teaching-learning spaces, the pandemic has exposed great difficulties related to digital infrastructure, as well as a gap -not only generational but also economic- that make it impossible to ensure the continuity of a thorough and quality educational process.